A Research on the Impacts of the Young People’s Internet Addiction Levels and their Social Media Preferences - Akın, Murat (International Review of Management and Marketing, 2017)
The aim of this study is to determine whether or not internet addiction levels of young people lead to differences in social media use intentions. The study consists of two main parts. In the literature review section where the conceptual framework is tried to be formed, internet addiction and social media concepts are defined, and information on social media use is given. Following the conceptual framework, the hypothesis to test whether or not the addiction has led to differences in the intended use is analyzed with a sample of 756 participants. The results of the research study suggest that 96.8% of the young people use the Internet on a daily basis, 91.2% use mobile phones for the Internet access, 0.61 of the young people are addicted to it, and 0.391 of them spend 5 - 6 hours online every day. Facebook is seen as the most preferred social media tool. Young people use the social media mostly to establish communication and to make various kinds of sharing. It is worried that the young people’s quality of life and mental health may be negatively affected in the later years. For this, first of all, the government needs to conduct studies on media literacy and create different social fields such as sports facilities, theaters, etc. where the young people can socialize with each other. In the conclusion of the study, the effects in question are evaluated, and the state, business managers, marketing researchers and marketing researchers are presented with suggestions. Keywords: Satisfaction, Behavioral and Attitudinal Brand Loyalties, Mobile Phone, Young Consumers JEL Classification: L2